ANALISIS DETERMINAN TINGKAT KEMISKINAN PADA MASA PRE-POST PANDEMI COVID-19 DI PROVINSI JAWA TIMUR - Asqalani, Muhammad Hafidh; Fitanto, Bahtiar (Journal of Development Economic and Social Studies, 2024)
The COVID-19 pandemic has wielded a significant economic impact, spanning from the global stage to the national and regional levels. This crisis has led to a slowdown in economic activity in East Java Province, resulting an increase in poverty rates. The pandemic's arrival in 2020 brought about substantial and unprecedented changes to the factors influencing poverty levels, presenting significant challenges for the East Java Provincial Government. The aim of this research is to analyze the influence of the Human Development Index, Population Growth, Economic Growth, and the COVID-19 Pandemic on the poverty rate in the districts/cities of East Java Province. This research employs panel data regression analysis using secondary data from 2017 to 2021 sourced from the Central Statistics Agency (BPS). The results found that the human development index had a negative and significant effect on poverty levels, economic growth and the COVID-19 pandemic had a positive and significant effect on poverty levels, while population growth was found to have no significant effect on poverty levels in East Java Province.